Effect of 5-E Model of Teaching on Higher Order Thinking Skills in Science at the Upper Primary Level - Mohalik, Ramakanta; Behera, Subhashree (JOURNAL OF INDIAN EDUCATION, 2018)
This study intended to find out the effectiveness of the 5-E model of teaching on higher order thinking skills (analysing, evaluating and creating) in science at the upper primary level. The pre test-post test single group experiment was conducted on 22 Class VII students of Nayagarh Girls’ High School, Odisha, India. The investigators taught 15 lessons based on the 5-E Learning Model for the Chapter—Light, of Class VII, Board of Secondary Education, Odisha. The self developed test on higher order thinking skills in science having 30 items was used as the tool. The study found that there is a significant improvement in the higher order thinking skills of students taught by the 5-E model of teaching at 0.01 levels. The study has suggested many implications for the teacher, Teacher Educators, textbook writers and policymakers.